Comparison of the level of vitamin D in preterm infected and uninfected infants - Zakerihamidi, Maryam; Boskabadi, Hassan; Faramarzi, Raheleh (Infekt͡s︡ii͡a︡ i immunitet, 2023)
Introduction. Despite the substantial progress in intensive cares, sepsis is still an important cause of neonatal mortality. Given the role of vitamin D in infection control, this study was conducted to compare vitamin D level in infected and uninfected preterm infants. Materials and methods. This cross-sectional study was carried out on 87 preterm infants (45 infected infants and 42 uninfected infants) hospitalized in Mashhad Ghaem Hospital, Iran, during 20152017. The subjects were selected by using convenience sampling. The infected infants (n = 45) included babies with clinical and laboratory findings compatible with infection and/or positive blood or cerebrospinal fluid cultures. The serum levels vitamin D were measured in all infants. A researcher-made questionnaire containing demographic, clinical and laboratory features of infants was used. In addition, independent t-test and chi-square test were applied. SPSS was used to perform the statistical data analysis. Results. 83% of infants had vitamin D deficiency 34.5%, 26.4%, and 21.8% of whom exhibited severe (less than 10 ng/ml), moderate (10.120 ng/ml), mild deficiency (20.130 ng/ml), respectively. The mean vitamin D level of infants was 23.319.40 ng/ml in the control group and 11.028.64 ng/ml in the case group (p = 0.000). In the case group, the mean vitamin D was 8.145.53 ng/ml in early sepsis and 12.629.75 ng/ml in late-onset sepsis (p = 0.121). 95% of infected infants and 71% of uninfected infants had vitamin D less than 30 ng/ml (p = 0.003). Conclusion. Vitamin D deficiency is very common in preterm infants. Serum vitamin D levels in infants with sepsis were lower than those in uninfected infants. Therefore, the correction of vitamin D deficiency may contribute to better control of neonatal infection.